Magnitude of visual impairment, blindness and causes in the southwest region of Sao Paulo state, Brazil - Schellini, Silvana Artioli [UNESP]; Fernandes de Souza Meneghim, Roberta Lilian [UNESP]; Satto, Larissa [UNESP]; Cavinatto, Pedro [UNESP]; Galindo-Ferreiro, Alicia; Khandekar, Rajiv (Consel Brasil Oftalmologia, 2018)
Purposes: The purpose of this study was to evaluate the magnitude and determinants of bilateral blindness and visual impairment (VI) in the southwest region of Sao Paulo State, Brazil. Methods: This cross-sectional study conducted during 2013 and 2014 targeted people of all ages in 10 districts in the southwest region of Sao Paulo State, Brazil. Ophthalmologists in a mobile unit measured visual acuity and examined eyes. Visual acuity was categorized according to the World Health Organization sex-adjusted rates with 95% confidence intervals (CI) were calculated. Number of blindness and visually impaired was projected for the entire study area. Results: We examined 2,306 participants. The age- and sex-adjusted frequency of bilateral blindness was 0.26% (95% CI: 0.1-0.4). Females (0.35%) and patients >= 50 years old (0.58%) had higher rate of blindness compared with males and younger individuals. The rate of severe VI was 9.1% (95% CI: 8.8-10.6) and was higher among males (11.6%) and those >= 50 years (12.3%). There could be 880 people with bilateral SVI in the study area. Bilateral severe VI was attributed to cataracts in 63% and was attributed to refractive error in 18%. Conclusion: Visual impairment and blindness in the study population was low and mainly due to cataract and refractive errors. Initiatives should be addressed by health care services to further reduce avoidable blindness in the region.
Keywords: Visual impairment; Blindness; Cataract; Refractive errors; Brazil